ACCOUNTING EDUCATION AND THE FORD AND CARNEGIE REPORTS. - Werntz, William W. (The Accounting Review, 1961)
Abstract The further a man goes in accounting, whether public or private, the more his technical knowledge as an accountant merges into and, at times, become an almost indistinguishable part of his knowledge and ability as a businessman or a businessman's consultant. But the qualified professional today can not be merely a technician. He must also be an educated man in the true sense of the word. The formal accounting education courses, i.e. a curriculum at the college level leading to a bachelor's degree with a major in accounting, are intended to qualify the graduate for entrance into the beginning levels of his profession as an accountant. The author opines that formal education in accounting should not be regarded as an end in itself but rather as a quicker and more efficient means of acquiring necessary knowledge. He references the Ford and Carnegie reports and attempts to answer–How great a cost in terms of time and effort can a young man afford to spend in formal education and how much should be left to be obtained through self-education and experience? He also attempts to explore the parts of the desired level of general and technical education that can best and most efficiently be handled formally and the parts, that are more efficiently left to self-education or to experience and on-the-job training?